Structured Counselling and Regular Telephonic follow up to improve Referral flow and compliance in Nepal for Diabetic Retinopathy(SCREEN-D Study): a randomised controlled trial - Binita Bhattarai; Hari Bahadur Thapa; Sandip Bashyal; Sarasawati Khadka Thapa; Sirshendu Chaudhuri; Varun Agiwal; Hira Pant; Samiksha Singh; Hemant Mahajan (BMC Health Services Research, 2024)
Abstract Background Diabetic Retinopathy (DR) is an emerging public health issue, leading to severe visual impairment or blindness. Early identification and prompt treatment play a key role in achieving good visual outcomes. The objective of the study was to estimate the effectiveness of SCREEN package on improving referral compliance from peripheral centres to a tertiary eye centre in Nepal. Methods In this facility-based cluster-randomized trial, ten out of 19 referring centres of the tertiary eye care centre in Lumbini zone, Nepal were randomized into intervention and control groups. A SCREEN packagewereprovided as intervention for DR patients who require advanced treatment in the tertiary centres and was compared with the current practice of the control arm, where structured counselling and follow-up mechanism are absent. Compliance was estimated by a weekly follow-up between the referring centre and the referred hospital. Results We recruited 302 participantsof whom 153 were in the intervention arm. The mean age of the participants was 57.8 years (Standard deviation [SD]±11.7 years). With implementation of SCREEN package71.2% (n=109) in the intervention group and 42.9% (n=64) in the control group were compliant till three months of follow-up (Difference 28.3%, 95% CI: 17.6- 39.0, p<0.05). Compliance was 43% (n=66) with counselling alone, and 66% (n=103) with first telephonic follow-up in the intervention arm. The mean duration to reach the referral centre was 14.7 days (SD± 9.4 days) and 18.2 days (SD± 9.1 days) in the intervention and the control arm, respectively (Difference 3.5 days, 95% CI: 0.7 to 6.4 days). Conclusions Counselling& follow-up to patients is the key factor to improve the utilization of the health services by patients with DR. Health systems must be strengthened by optimizing the existing referral structure in Nepal. Trial registration ClinicalTrials.gov Protocol Registration and Results System, ClinicalTrials.gov Identifier: NCT04834648 , 08/04/2021.